2014
DOI: 10.17221/7779-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Influence of protected organic acid blends and diets with different nutrient densities on growth performance, nutrient digestibility and faecal noxious gas emission in growing pigs

Abstract: ABSTRACT:This study was conducted to evaluate the effects of dietary supplementation of protected organic acid blends including medium chain fatty acids and different nutrient density diets on growth performance, nutrient digestibility and faecal noxious gas content in growing pigs. A total of 80 crossed [(Landrace × Yorkshire) × Duroc] growing pigs with an initial body weight (BW) of 22.61 ± 2.32 kg were used in a six-week trial. Pigs were randomly allocated into one of four treatment groups in a 2 × 2 factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
3
27
0
3
Order By: Relevance
“…Our results are in agreement with previous experiments that showed feeding a diet supplemented with protected OA blends, improved ADG, feed efficiency and did not affect ADFI (Upadhaya et al 2014(Upadhaya et al , 2015b. It has been reported that the addition of single or blends of OA may have a negative effect on the palatability of the diet, thus decreasing ADFI (Walsh et al 2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with previous experiments that showed feeding a diet supplemented with protected OA blends, improved ADG, feed efficiency and did not affect ADFI (Upadhaya et al 2014(Upadhaya et al , 2015b. It has been reported that the addition of single or blends of OA may have a negative effect on the palatability of the diet, thus decreasing ADFI (Walsh et al 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies indicate microencapsulation would increase the effects of OA and EO (Burnell et al 1988;Cho et al 2014;Zhang et al 2014;Mohammadi Gheisar et al 2015;Upadhaya et al 2015a,b;Mohana Devi et al 2016). The effects of micro-encapsulated organic acids and essential oils (MOE) in pigs and poultry have been variable because of different study conditions and differences in the type of MOE used as well as variation in the dose provided (Zhang et al 2005;Upadhaya et al 2014;Mohammadi Gheisar et al 2015;Lee et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous reports, the dietary supplementation of a microencapsulated organic acid blend with inorganic acids such as MCFAs or essential oil had positive effects on the growth performance and nutrient digestibility in growing (13) and finishing pigs (14,15), but not yet in layer hens. Thus, the objective of the present study was to evaluate the effects of a microencapsulated organic acid blend with MCFAs on egg production, weight, quality, fecal microflora, and nutrient digestibility in laying hens.…”
Section: Introductionmentioning
confidence: 89%
“…OA have previously been used in weanling pigs and are known to improve nutrient digestibility and growth performance (Upadhaya et al 2014), and to modify the intestinal microflora . It has been reported that OA added to the diets of young chicks altered the microbial population of the small intestine (Cengiz et al 2012).…”
mentioning
confidence: 99%